Lesson Planning - Mishra, R.C. (India, 2007)
The book is designed for those teachers who find it incumbent to influence.new life into their teaching methodologies. Elaborating on the various reasons due to which students find it difficult to focus their.con-centration it equips teachers with various skills which they could adopt while planning out the lessons to be taught.
Keywords: Lesson Plan; Lesson Planning